BRET-based biosensors for SARS-CoV-2 oligonucleotide detection - Sultana, Asfia; Geethakumari, Anupriya M.; Islam, Zeyaul; Kolatkar, Prasanna R.; Biswas, Kabir H. (Frontiers in Bioengineering and Biotechnology, 2024)
The need for early detection of emerging pathogenic viruses and their newer variants has driven the urgent demand for developing point-of-care diagnostic tools. While nucleic acid-based methods such as reverse transcription-quantitative polymerase chain reaction (RT-qPCR), loop-mediated isothermal amplification (LAMP), and other methods have been developed, a more facile and robust platform remains required. To address this need, as a proof of principle study, we engineered a prototypeversatile, sensitive, rapid, and cost-effective Bioluminescence Resonance Energy Transfer (BRET)based Biosensor for Oligonucleotide Detection (BioOD). Specifically, we designed BioODs against SARS-CoV-2 parental (Wuhan strain) and the B.1.617.2 delta variant through the conjugation of specific, fluorescently modified molecular beacons (sensor module) through a complementary oligonucleotide handle DNA functionalized with NanoLuc (NLuc) luciferase protein such that dissolution of the molecular beacon loop upon binding of viral oligonucleotide will result in a decrease in BRET efficiency and thus, a change in the bioluminescence spectra. Following the assembly of the BioODs, we determined their kinetics response, affinity for variant-specific oligonucleotides, and specificity and found them to show rapid and highly specific. Further, the decrease in BRET efficiency of the BioODs in the presence of viral oligonucleotides can be detected as a change in color in cell phone camera images. We envisage that the BioODs developed here will find application in detecting viral infections with variant-specificity in a point-of-care-testing format, thus aiding in large-scale viral infection surveillance.